Effect of Coffee Grounds Waste Application on the Growth of Green Grass Jelly Cuttings (Premna oblongifolia Merr.) - Alif Abdullah Zakaria; Dirgahani Putri; Rosdiana Rosdiana; Sukrianto Sukrianto (Open Global Scientific Journal, 2026)
Background: The quality of green grass jelly cuttings can be improved through fertilization. Coffee grounds waste is one alternative material that can be used as a fertilizer. The organic carbon (C), nitrogen (N), phosphorus (P), and potassium (K) content of coffee grounds waste has been reported to support plant growth in previous studies. However, the appropriate application rate of coffee grounds waste for supporting the growth of green grass jelly cuttings has not yet been clearly established.Aims: This study aimed to determine the effect of coffee grounds waste application rates on the growth of green grass jelly cuttings.Methods: The study was conducted from March to May 2023 in Talagening, Bobotsari, Purbalingga, Central Java, Indonesia. A randomized complete block design (RCBD) was used with six treatments: NPK fertilizer at 3 g polybag⁻¹ and coffee grounds waste at 10, 20, 30, 40, and 50 g polybag⁻¹. Data were analyzed using an F-test, followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level when significant differences were observed.Results: Coffee grounds waste application promoted the growth of green grass jelly cuttings. The application rate of 40 g polybag⁻¹ was effective in increasing the number of shoots, shoot height, number of leaves, leaf length, leaf width, number of roots, and fresh weight of the cuttings.Conclusion: Coffee grounds waste at 40 g polybag⁻¹ was an effective application rate for promoting the growth of green grass jelly cuttings.